Cover Jurnal Fitopatologi Vol. 17 No. 2, Maret 2021 - Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page and back cover of the Indonesian Journal of Phytopathology, Volume 17, No. 2, March 2021.